Optimization of Planting Distance for the Growth and Yield of Red Beetroot (Beta vulgaris L.) at Various Harvest Ages - Widiwurjani; Rr. Djarwatiningsih Pongki.S; Dewi Mayangsari (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Red beet (Beta vulgaris L.) is a horticultural crop whose production remains limited in Indonesia. Therefore, it isnecessary to increase productivity by optimizing planting distance and harvest age. This study aimed to examinethe interaction between planting distance and harvest age on the growth and yield of the red beet variety Ayumi04. The research was conducted from March to June 2025 in Mojoroto Village, Pacet District, Mojokerto, using aRandomized Block Design (RBD) with two treatment factors: planting distance and harvest age. The first factorwas planting distance (30x30 cm, 30x25 cm, 30x20 cm, 30x15 cm), and the second factor was harvest age (50, 60,and 70 days after sowing [DAS]). Observed parameters included plant length, leaf area, fresh tuber weight perplant, fresh tuber weight per plot, tuber weight per hectare, and leaf area index. The results showed that aplanting distance of 30x15 cm combined with a harvest age of 70 DAS produced the best results, with fresh tuberweight per plot of 3.90 kg and per hectare of 27.06 tons/ha. These findings provide practical guidance indicatingthat a 30x15 cm planting distance and a 70 DAS harvest age are optimal for enhancing land-use efficiency and redbeet production. Overall, appropriate planting distance and harvest timing can significantly improve theproductivity and yield of red beetroot.